Climate change: A potential risk to cage culture and genetic structure of native fisheries in fish cage‐installed inland lakes. Issue 3 (28th July 2020) - Oyebola, Oyediran Olusegun; Fada, Pentecost Ozemoya
Abstract: Fish cage aquaculture (FCA) in lakes is a viable climate change (CC) mitigation approach; however, deficiencies in monitoring, early warning and risk planning could threaten its sustainability. Thus, the present study focused on examining the experiences with CC and its risks to cage fish culture, and phenotypic structure of a typical endemic fishery in fish cage‐installed (FCI) and fish cage‐free (FCF) lakes. Using a structured questionnaire, fisherfolks of typical FCI and FCF lakes in southwestern Nigeria were consulted for their local experiences regarding CC variables, effects on cage aquaculture and the occurrence of caged fish in their fish catches. For phenotypic structure analysis, size cohorts of cage‐cultured (CCU) and wild‐caught (WC) Oreochromis niloticus from FCI (CCU FCI and WCFCI), and WC from FCF (WCFCF) were obtained and analysed for phenotypic differences ( p  < .05) and mix‐up through cluster/linkage analysis. Respondents experienced unpredictable climatic conditions, increased rainfall fluctuations and declining rainfall (86.4; 47.1%, 50.0; 64.7%, 100.0; 88.2%, in FCI and FCF lakes, respectively), indicating that CC affects cage culture, induces cage damage and floods, and results in caged fish escapes (40.9; 35.3%, 81.8; 11.8%, 95.5; 41.2% in FCI and FCF lakes, respectively), while caged fishes occur in fisherfolks' catches (63.6% FCI). Phenotypically, WCFCF and WCFCI were similar, but differed from CCU FCI for pre‐dorsal length. WCFCF and WCFCI differed for caudal peduncle lengths. In addition, some individuals of CCU FCI clustered with WCFCI and WCFCF, rather than their population cohorts. Climate change impacts on FCA lakes have implications regarding caged fish escapes. Phenotypic structures indicated a possible mix‐up of caged and wild O. niloticus populations. Thus, monitoring, control and surveillance (MCS) of cage culture in lakes is necessary, and development of genetic markers for endemic species would also facilitate MCS.